2020
DOI: 10.1177/1073110520958880
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences of Coverage Laws Targeting Cancer Drugs

Abstract: Why do cancer drugs get such an easy ride?" (Light and Lexchin, 2015). This question was originally asked about regulatory standards for approval, but it may be just as pertinent to cancer drugs' coverage in insurance plans. In a case study in Massachusetts, Leopold and colleagues identified several state laws targeting the coverage of cancer drugs in health insurance programs. Such "onco-exceptionalism" in coverage policy poses challenges for payers confronted with high-cost drugs with limited evidence on cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Under the proposed approach to impose terms and conditions on drug approvals more broadly, it can be expected that post market confirmatory trials will continue to be relied upon to address uncertainties that exist at the time of approval or that arise post-market. The examples discussed above confirm concerns expressed previously in other jurisdictions that post market confirmatory trials should not be relied upon to address uncertainties under existing regulatory structures (66).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Under the proposed approach to impose terms and conditions on drug approvals more broadly, it can be expected that post market confirmatory trials will continue to be relied upon to address uncertainties that exist at the time of approval or that arise post-market. The examples discussed above confirm concerns expressed previously in other jurisdictions that post market confirmatory trials should not be relied upon to address uncertainties under existing regulatory structures (66).…”
Section: Discussionsupporting
confidence: 72%
“…Similar findings have been found for drug approvals more generally; one study found that that the proportion of approvals supported by only single-group pivotal trials has increased from 1995 to 2017 (74). Furthermore, several studies have found that approving drugs with limited clinical evidence, once intended to be the exception has instead become the new norm (66,75,76). Notwithstanding a literal reading of the new regulatory approach, it seems unlikely that Canada will stop exercising flexibility to approve drugs with promising evidence and start requiring strict adherence to regulatory requirements requiring substantial evidence of clinical effectiveness.…”
Section: How Can the Current Noc/c Pathway Inform The Proposed Agile ...supporting
confidence: 66%
“…21 That the public and other regulators are privy only to the end result without visibility or knowledge about the deliberations regarding the benefit-risk evaluation that leads up to the final result is unsatisfactory from a transparency and confidence perspective. This is particularly important for products for which decision making is a challenge, 22 as in this study in which alectinib hydrochloride was approved as conditional by the EMA but given accelerated approval by the FDA and cangrelor initially received a complete response letter from the FDA. Transparency on the factors behind the decision may become a challenge in cases in which the application of formal weightings to the various components of the benefit-risk matrix is not clearly documented.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are especially important for innovative or technologically challenging products for which experience in evaluating similar products worldwide is limited. 22 This transparency is becoming increasingly important as agencies are striving to build effective and efficient regulatory processes by leveraging assessments by trusted reference agencies through approaches such as work sharing and reliance pathways. Transparent communication and documentation of the decisions in the PAR are central and should continue to evolve as a best practice that should be adopted by agencies worldwide.…”
mentioning
confidence: 99%
“…Finally, we must ask whether cancer is somehow morally special, such that it justifiably commands unlimited resources while all other health care needs are subject to cost constraints. This has recently been referred to as “onco-exceptionalism,” and is regarded as being ethically problematic (Salcher-Konrad and Naci 2020 ; Fu et al 2021 ).…”
Section: Solidarity: the Challenge Of Limited Resourcesmentioning
confidence: 99%